Digital Workerism: Technology, Platforms, and the Circulation of Workers’ Struggles - Sai Englert; Jamie Woodcock; Callum Cant (tripleC: Communication, Capitalism & Critique)
The use of digital technology has become a key part of contemporary debates on how work is changing, the future of work/ers, resistance, and organising. Workerism took up many of these questions in the context of the factory – particularly through the Italian Operaismo – connecting the experience of the workplace with a broader struggle against capitalism. However, there are many differences between those factories and the new digital workplaces in which many workers find themselves today. The methods of workers’ inquiry and the theories of class composition are a useful legacy from Operaismo, providing tools and a framework to make sense of and intervene within workers’ struggles today. However, these require sharpening and updating in a digital context. In this article, we discuss the challenges and opportunities for a “digital workerism”, understood as both a research and organising method. We use the case study of Uber to discuss how technology can be used against workers, as well as repurposed by them in various ways. By developing an analysis of the technical, social, and political re-composition taking place on the platform, we move beyond determinist readings of technology, to place different technologies within the social relations that are emerging. In particular, we draw attention to the new forms through which workers’ struggles can be circulated. Through this, we argue for a “digital workerism” that develops a critical understanding of how the workplace can become a key site for the struggles of digital/communicative socialism.